PERSEPSI MASYARAKAT KOTA MANADO TENTANG KEBIJAKAN MANADO FIESTA (STUDI DI BEBERAPA KECAMATAN DI KOTA MANADO) - Silaen, Lutden; Posumah, Johnny Hanny; Palar, Novie Anders (Sam Ratulangi University, 2018)
Abstract: In the Manado Fiesta, policy seen and felt by local people through the five senses of sight, but not allpublic opinion says good or bad about Manado Fiesta Policy, because every individual has different perceptionsor views. Manado fiesta is a program of Manado City Tourism event that is the agenda of Wonderful Indonesiaactivities in 2017 Manado Fantastic Festival (MFF). Manado Fiesta is a tourism activity of Manado City thathas been launched in Ministry of Tourism of Republic of Indonesia. The purpose of this research is to knowhow Manado perception about Manado Fiesta Policy (Study in Several Subdistrict In Manado City). Thisresearch used descriptive method of qualitative approach by describing data obtained from research result aboutManado City people perception about Manado Fiesta policy (Study in Several Subdistrict In Manado City).Manado Fiesta is a tourism activity of Manado City which has been launched in Ministry of Tourism ofRepublic of Indonesia. The purpose of this study is to find out how the perception of Manado City people aboutManado Fiesta Policy (Study in Several Districts In Manado City).This research used descriptive method ofqualitative approach by describing data obtained from research result about Manado City people perceptionabout Manado Fiesta Policy (Study in Several Subdistrict In Manado City).The overall conclusion of ManadoCity Manpower's perception of Manado Fiesta Policy (Study in Several Sub-districts of Manado City) is quitegood because still new program implemented in Manado city has many flaws. Then some things that can besuggested is to Manado City Government need to strengthen the law of Manado Fiesta implementation bymaking and arranging about Manado Fiesta to officially become an annual event in Manado City. The needfor the government to be more leverage for the implementation of the next year to evaluate and overcome theproblems of past implementation, Improvement Management of the implementation including the location ofManado Fiesta implementation location of the need for supporting facilities for visitors to comfortably followManado Fiesta. The government also provides opportunities and facilitates local people to sell artworks tovisitors.Keywords: Perception, Manado Fiesta Policy